Analysis of the Influence of Service and Product Quality on Repurchase Intensity through Customer Satisfaction Mediation of the Nasi Jamblang Mangdul Eating House - Abdur Rafiq; Minto Waluyo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In an era of increasingly sharp competition, marketers need to improve product quality and service quality to emerge as winners in the competition. Nasi Jamblang is a typical Cirebon culinary dish characterized by the use of teak leaves as a wrapper or serving dish. The name Jamblang itself is the name of an area in Cirebon district. Nasi Jamblang has a variety of side dishes, including fried chili sauce, vegetable tofu, lungs, liver or meat stew, pergedel, potato satay, omelet, fried egg, fish stew, salted fish, tofu and tempeh, blekutak. The quality of a product is related to function, accuracy, and reliability. This research aims to determine the effect of service level and product quality on consumer satisfaction, which then influences repeat purchase interest at Nasi Jamblang Mangdul Restaurant. The research results obtained by researchers for the very good category were 43%, the good category was 40%, the enough 17%, and the less than 0% category.